Determinants of Organizational Performance and its Implications on Sustained Competitive Advantage: Empirical Study in Indonesian Television Media Companies - Oscar Jayanagara; Kelly Azaryas Chen (Universitas Pelita Harapan, 2024)
This research aims to analyze the effect of Organizational Culture, Top Succession Context, and Information Communication Technology Strategy on Organizational Performance, and their implication to Sustained Competitive Advantage. The methodology of this research was quantitative research with hypothesis testing for examining seven hypotheses. Populations were the 12 national broadcasting companies, which were located in DKI Jakarta, with sample size were 260 television workers. Data for this study were collected using questionnaires and SEM (Structural Equation Modeling) was employed for data analysis techniques. The results of this research in general there was the effect of Organizational Culture, Top Succession Context, and Information Communication Technology Strategy on Organizational Performance, Top Succession Context, Information Communication Technology Strategy, and Organizational Performance on Sustained Competitive Advantage of twelve television broadcasting companies of Indonesia. All of seven hypotheses which proposed in this research, six hypotheses were being given can be accepted, except Organizational Culture did not influence Sustained Competitive Advantage. Information Communication Technology Strategy as an independent variable was the strongest influence on Organizational Performance and Sustained Competitive Advantage. This research also provides discussion on the findings as well as limitations, theoretical and practical contribution, theoretical and managerial implications of the study, and suggestions for future research.